Peningkatan Kecakapan Digital Pada Siswa SD Inpress Kolorai Kabupaten Pulau Morotai Maluku Utara - Sabban, Irawati (Kreativasi : Journal of Community Empowerment, 2023)
The purpose of this service is to provide knowledge and instill digital attitudes and skills to the students of the Inpres Elementary School in Kolorai Village, Morotai Island Regency, North Maluku Province. This service is important to do in Kolorai Village because the village has a uniqueness on a small island and the village is designated as one of the marine villages by the Morotai Island Regency Government. This activity is carried out through three stages, namely planning, implementation, and evaluation. The method used is a comment poster. As a nautical village, of course, digital skills must be given from the time the child is of primary school age, it's just that this island has not been supported by infrastructure. What digital kids understand is content and social media accounts. This activity really provides a learning experience for the students of SD Inpres Kolorai because most of them are active users of friendship applications and content that feeds city life. So that students can understand that everything learned from the accounts and applications they are happy with today can have a negative impact on themselves and their environment. So that they can do positive things, as well as protect themselves from newly recognized people through gadgets.